Design, Synthesis and Biological Screening of Novel 1,5-Diphenyl-3-(4-(trifluoromethyl)phenyl)-2-pyrazoline Derivatives - KAYMAKÇIOĞLU, BEDİA; TOK, FATİH (SLOVENSKO KEMIJSKO DRUSTVO, 2020)
1-Phenyl-5-substituted-3-(4-(trifluoromethyl)phenyl)-4,5-dihydro-1H-pyrazole derivatives were synthesized from chalcone derivatives. The structures of compounds were characterized by IR, H-1 NMR spectroscopic methods and elemental analysis. All compounds were evaluated for their in vitro antioxidant activity using DPPH and ABTS methods, anti-inflammatory activity using lipoxygenase inhibitory method and antidiabetic activity using the alpha-glucosidase inhibitory method. Especially, pyrazoline derivatives exhibited stronger anti-inflammatory activity than the reference drug indomethacin (IC50: 50.45 mu M) and their IC50 values were in the range of 0.68 and 4.45 mu M. In addition, the ADME properties of all chalcone and pyrazoline derivatives were calculated by Lipinski's and Veber's rules.
Keywords: 2-Pyrazoline; lipoxygenase enzyme; alpha-glucosidase; ABTS and DPPH; ANTIOXIDANT; PYRAZOLINES; CHALCONE; FLUORINE; EXTRACTS; DOCKING; LEAF